RP-HPTLC PROFILING OF SECONDARY METABOLITES FROM FICUS BENJAMINA AND FICUS KRISHNAE - PUNEET KAUR; PAYAL MITTAL; RAJIV SHARMA (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objective: This study was carried out to measure the amounts of quercetin and rutin in the hydroalcoholic extracts of Ficus benjamina and Ficus krishnae leaves using high-performance thin layer chromatography (HPTLC). The results showed a clear separation of these two compounds from other substances in the extracts. The method used is fast, easy to perform, and provides accurate and reliable results. Methods: TLC plates coated with silica gel 60 F254 were used for the test, and each sample was applied at a speed of 150 nanoL/s. A CAMAG TLC Scanner III was used to scan the plates, with quercetin detected at 254 nm and rutin at 366 nm. The presence of these compounds in the samples was confirmed by comparing their UV spectra with those of the standard compounds. Quercetin and rutin were identified by their specific Rf values, 0.31 and 0.73, respectively. Results: HPTLC was utilized to differentiate F. benjamina and F. krishnae by analyzing their phytochemical profiles. Using silica gel 60 F254 plates, rutin and quercetin were separated with solvent systems toluene: ethyl acetate: formic acid (5:3.5:0.5) and toluene: chloroform:methanol (7:2.5:0.5), respectively. The compounds exhibited Rf values of approximately 0.31 for rutin and 0.73 for quercetin, facilitating their identification and quantification in the plant extracts. Conclusion: This study introduces a rapid, sensitive, and cost-effective HPTLC method for the routine quality assessment of herbal products. By quantifying quercetin and rutin in the leaves of F. benjamina and F. krishnae, as well as in related herbal formulations, the method supports the standardization and ensures the consistency of these plant-based preparations.